The prevalence and risk factors for pneumococcal colonization of the nasopharynx among children in Kilifi District, Kenya. - Osman Abdullahi; Angela Karani; Caroline C Tigoi; Daisy Mugo; Stella Kungu; Eva Wanjiru; Jane Jomo; Robert Musyimi; Marc Lipsitch; J Anthony G Scott (PLoS ONE)
Background Pneumococcal conjugate vaccines (PCV) reduce nasopharyngeal carriage of vaccine-serotype pneumococci but increase in the carriage of non-vaccine serotypes. We studied the epidemiology of carriage among children 3-59 months old before vaccine introduction in Kilifi, Kenya. Methods In a rolling cross-sectional study from October 2006 to December 2008 we approached 3570 healthy children selected at random from the population register of the Kilifi Health and Demographic Surveillance System and 134 HIV-infected children registered at a specialist clinic. A single nasopharyngeal swab was transported in STGG and cultured on gentamicin blood agar. A single colony of pneumococcus was serotyped by Quellung reaction. Results Families of 2840 children in the population-based sample and 99 in the HIV-infected sample consented to participate; carriage prevalence was 65.8% (95% CI, 64.0-67.5%) and 76% (95% CI, 66-84%) in the two samples, respectively. Carriage prevalence declined progressively with age from 79% at 6-11 months to 51% at 54-59 months (p<0.0005). Carriage was positively associated with coryza (Odds ratio 2.63, 95%CI 2.12-3.25) and cough (1.55, 95%CI 1.26-1.91) and negatively associated with recent antibiotic use (0.53 95%CI 0.34-0.81). 53 different serotypes were identified and 42% of isolates were of serotypes contained in the 10-valent PCV. Common serotypes declined in prevalence with age while less common serotypes did not. Conclusion Carriage prevalence in children was high, serotypes were diverse, and the majority of strains were of serotypes not represented in the 10-valent PCV. Vaccine introduction in Kenya will provide a natural test of virulence for the many circulating non-vaccine serotypes.